Westonci.ca is the Q&A platform that connects you with experts who provide accurate and detailed answers. Our platform provides a seamless experience for finding precise answers from a network of experienced professionals. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
To solve the equation [tex]\(\log_5(x + 2) = 1 - \log_5(x + 6)\)[/tex], we'll proceed with the following steps:
1. Isolate the logarithms on one side:
[tex]\[ \log_5(x + 2) + \log_5(x + 6) = 1 \][/tex]
2. Use the properties of logarithms:
Recall the property of logarithms that states [tex]\(\log_b(a) + \log_b(c) = \log_b(ac)\)[/tex]. Applying this property, we have:
[tex]\[ \log_5((x + 2)(x + 6)) = 1 \][/tex]
3. Convert the logarithmic equation to an exponential equation:
Recall that if [tex]\(\log_b(y) = c\)[/tex], then [tex]\(b^c = y\)[/tex]. So, we get:
[tex]\[ 5^1 = (x + 2)(x + 6) \][/tex]
4. Simplify and solve the quadratic equation:
[tex]\[ 5 = (x + 2)(x + 6) \][/tex]
Expand the right-hand side:
[tex]\[ 5 = x^2 + 6x + 2x + 12 \][/tex]
[tex]\[ 5 = x^2 + 8x + 12 \][/tex]
Subtract 5 from both sides to set the equation to zero:
[tex]\[ 0 = x^2 + 8x + 7 \][/tex]
5. Factor the quadratic equation:
We need to factor [tex]\(x^2 + 8x + 7\)[/tex]. Looking for two numbers that multiply to 7 and add up to 8, we get 1 and 7.
[tex]\[ 0 = (x + 1)(x + 7) \][/tex]
6. Solve for [tex]\(x\)[/tex]:
[tex]\[ x + 1 = 0 \quad \text{or} \quad x + 7 = 0 \][/tex]
[tex]\[ x = -1 \quad \text{or} \quad x = -7 \][/tex]
7. Check for valid solutions:
* For [tex]\(x = -1\)[/tex]:
[tex]\[ \log_5(-1 + 2) = \log_5(1) = 0 \][/tex]
[tex]\[ 1 - \log_5(-1 + 6) = 1 - \log_5(5) = 1 - 1 = 0 \][/tex]
Both sides are equal, so [tex]\(x = -1\)[/tex] is a valid solution.
* For [tex]\(x = -7\)[/tex]:
[tex]\[ \log_5(-7 + 2) = \log_5(-5) \][/tex]
The logarithm of a negative number is not defined, so [tex]\(x = -7\)[/tex] is not a valid solution.
Thus, the only valid solution is:
[tex]\[ x = -1 \][/tex]
1. Isolate the logarithms on one side:
[tex]\[ \log_5(x + 2) + \log_5(x + 6) = 1 \][/tex]
2. Use the properties of logarithms:
Recall the property of logarithms that states [tex]\(\log_b(a) + \log_b(c) = \log_b(ac)\)[/tex]. Applying this property, we have:
[tex]\[ \log_5((x + 2)(x + 6)) = 1 \][/tex]
3. Convert the logarithmic equation to an exponential equation:
Recall that if [tex]\(\log_b(y) = c\)[/tex], then [tex]\(b^c = y\)[/tex]. So, we get:
[tex]\[ 5^1 = (x + 2)(x + 6) \][/tex]
4. Simplify and solve the quadratic equation:
[tex]\[ 5 = (x + 2)(x + 6) \][/tex]
Expand the right-hand side:
[tex]\[ 5 = x^2 + 6x + 2x + 12 \][/tex]
[tex]\[ 5 = x^2 + 8x + 12 \][/tex]
Subtract 5 from both sides to set the equation to zero:
[tex]\[ 0 = x^2 + 8x + 7 \][/tex]
5. Factor the quadratic equation:
We need to factor [tex]\(x^2 + 8x + 7\)[/tex]. Looking for two numbers that multiply to 7 and add up to 8, we get 1 and 7.
[tex]\[ 0 = (x + 1)(x + 7) \][/tex]
6. Solve for [tex]\(x\)[/tex]:
[tex]\[ x + 1 = 0 \quad \text{or} \quad x + 7 = 0 \][/tex]
[tex]\[ x = -1 \quad \text{or} \quad x = -7 \][/tex]
7. Check for valid solutions:
* For [tex]\(x = -1\)[/tex]:
[tex]\[ \log_5(-1 + 2) = \log_5(1) = 0 \][/tex]
[tex]\[ 1 - \log_5(-1 + 6) = 1 - \log_5(5) = 1 - 1 = 0 \][/tex]
Both sides are equal, so [tex]\(x = -1\)[/tex] is a valid solution.
* For [tex]\(x = -7\)[/tex]:
[tex]\[ \log_5(-7 + 2) = \log_5(-5) \][/tex]
The logarithm of a negative number is not defined, so [tex]\(x = -7\)[/tex] is not a valid solution.
Thus, the only valid solution is:
[tex]\[ x = -1 \][/tex]
We hope our answers were helpful. Return anytime for more information and answers to any other questions you may have. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.